Mission and Engagement of The Vincentians to Priestly Formation in Indonesia: A Historical-Theological Revisit - Lorentius Iswandir; FX Eko Armada Riyanto (International Journal of Indonesian Philosophy & Theology, 2020)
This paper explores historical engagement in priestly formation in Indonesia by the Vincentians, the Catholic Religious Congregation, who has been sent to a mission in Indonesia (from the Netherlands) and erected the Diocese of Surabaya since 1923. The paper outlines the Vincentian missionaries’ theological understanding of mission and the importance of establishing minor and major seminary to train the indigenous candidates for the priesthood to take care of their local churches. This study's methodology applies a historical approach to see the strategies of the Vincentians to develop the formation of priestly candidates related to the challenges of the times. From this study, we found that the history of the Catholic mission has a meaningful peak in planting the Church as often produced in the mission and the formation of its local priests. The education of candidates for the priesthood is not just a form of apostolic work but is essentially a necessary part of the Catholic Church's mission. The Vincentians have carved a hard work of mission apostolates in the establishment of the Diocese of Surabaya with its charismatic works and the education of its laymen until today and especially in the continual engagement in the priestly formation in Indonesia with its changing challenges. The excellent form of the Catholic priests is essential to the mission, as the candidates will be the future leaders of the local Church and the preachers of the Gospel wherever they are sent.